Organizing Public Health Services Based on Best Practice Study of the "Layad Rawat" Innovation Program in Bandung - Adiguna, Aditya Putera; Rahmawati, Dian Eka (Jurnal Ilmiah Tata Sejuta STIA Mataram, 2020)
This research is motivated by the efforts of the Bandung City Government in improving the quality of health services that have been conducted conventionally, citizens must visit a health facility to be served. The problems of a city, especially the city of Bandung have developed so complex that conventional solutions are often not able to overcome the problems in health care, so more innovative solutions are needed to solve health service problems in Bandung. The innovation was named Layad Rawat. Through this program, Bandung City has sought to improve health services and facilitate community needs. Data collection techniques, carried out by in-depth interviews with the Department of Health and UPT P2KT, official regulations. The results showed the Layad Rawat program was accordance with best practice criteria, seen from the results of the program, partnerships with the private sector, the role of mayor Bandung city, equality to access services, sustainability, and adoption by other regions . Through Layad Rawat, people in Bandung City no longer have difficulty in getting access to health services, only calling the Call Center 119. Layad Rawat innovation practices in improving the quality of health services in Bandung City is the best solution in responding the problems. Keywords: Innovation, Health Service, Layad Rawat